Communication Abilities, Assessment Procedures, and Intervention Approaches in Rett Syndrome: A Narrative Review - Louiza Voniati; Angelos Papadopoulos; Nafsika Ziavra; Dionysios Tafiadis (Brain Sciences, 2025)
Background/Objectives: Rett syndrome (RTT) is a rare neurodevelopmental disorder that affects movement and communication skills primarily in females. This study aimed to synthesize the research from the last two decades regarding the verbal and nonverbal communication abilities, assessment procedures, and intervention approaches for individuals with RTT. Methods: A structured literature search was conducted using the Embase, Scopus, and PubMed databases. Fifty-seven studies were selected and analyzed based on inclusion criteria. The data were categorized into four domains (verbal communication skills, nonverbal communication skills, assessment procedures, and intervention approaches). Results: The findings indicated a wide variety of communicative behaviors across the RTT population, including prelinguistic signals, regression in verbal output, and preserved nonverbal communicative intent. Moreover, the results highlighted the importance of tailored assessments (Inventory of Potential Communicative Acts, eye tracking tools, and Augmentative and Alternative Communication) to facilitate functional communication. The individualized intervention approaches were found to be the most effective in improving communicative participation. Conclusions: The current review provides an overview of the current evidence with an emphasis on the need for personalized and evidence-based clinical practices. Additionally, it provided guidance for professionals, clinicians, and researchers seeking to improve the quality of life for individuals with RTT.